The Potential and Problems of Bakutaru Disadvantaged Villages: Economic, Social, and Ecological Resilience in a Sociological Perspective - Arsyad, Muhammad; Peribadi; Gultom, Laode Monto (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study uses a qualitative approach with sociological analysis to evaluate the potential and problems of Bakutaru Disadvantaged Villages. Field observations, in-depth interviews, and document analysis were conducted to collect data on local businesses, skills training, economic, social, and ecological conditions of the village. The results of the study show that the diversification of economic activities has potential, but is constrained by limited infrastructure. Village social capital is strong, but minimal social infrastructure hinders cooperation. Basic education is quite good, but non-formal and supporting educational facilities are still lacking. Health services are adequate, but the low participation of BPJS indicates the need to increase health insurance. Ecological challenges include high pollution and minimal disaster management. This research makes an important contribution to development and science by demonstrating the need for effective interventions to improve the economic, social, and ecological resilience of Bakutaru Disadvantaged Villages, South Konawe district, Southeast Sulawesi